Clinical Corneal Optical Coherence Elastography Measurement Precision: Effect of Heartbeat and Respiration - Lan, Gongpu (Transl Vis Sci Technol, 2020)
PURPOSE: Normal physiological movements (e.g., respiration and heartbeat) induce eye motions during clinical measurements of human corneal biomechanical properties using optical coherence elastography (OCE). We quantified the effects of respiratory and cardiac-induced eye motions on clinical corneal OCE measurement precision and repeatability. METHODS: Corneal OCE was performed using low-force, micro-air-pulse tissue stimulation and high-resolution phase-sensitive optical coherence tomography (OCT) imaging. Axial surface displacements of the corneal apex were measured (M-mode) at a 70-kHz sampling rate and three different stimulation pressures (20–60 Pa). Simultaneously, the axial corneal position was tracked with structural OCT imaging, while the heartrate and respiration were monitored over a 90 second period. RESULTS: Respiratory- and cardiac-induced eye motions have distinctly lower frequency (0.1–1 Hz) and much greater amplitude (up to ± 50 µm movements) than air-pulse-induced corneal tissue deformations (∼250 Hz, <1 µm). The corneal displacements induced during OCE measurements in vivo were –0.41 ± 0.06 µm (n = 22 measurements, coefficient of variation [CV]: 14.6%) and –0.44 ± 0.07 µm (n = 50 measurements, CV: 15.9%), respectively, from two human subjects at 40 Pa stimulation pressure. Observed variation in corneal tissue displacements were not associated with tissue stimulation magnitude, or the amplitude of physiologically induced axial eye motion. CONCLUSIONS: The microsecond timescale and submicron tissue displacements observed during corneal OCE measurements are separable from normal involuntary physiological movements, such as the oculocardiac pulse and respiratory movements. TRANSLATIONAL RELEVANCE: This work advances innovations in biomedical imaging and engineering for clinical diagnostic applications for soft-tissue biomechanical testing.